2015
DOI: 10.1016/j.compscitech.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Photo-polymerization, swelling and mechanical properties of cellulose fibre reinforced poly(ethylene glycol) hydrogels

Abstract: a b s t r a c tThe application of hydrogels as load-bearing biomedical components is often limited by their mechanical properties. Often an attempt to improve a hydrogel's stiffness is accompanied by a loss of toughness and swelling properties. In this work, we show that the addition of nanofibrillated cellulose (NFC) provides a mean to tailor both the swelling and the mechanical properties of the hydrogel. Various volume fractions of NFC were added to poly(ethylene glycol) dimethacrylate (PEGDM) precursors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Hydrogel precursors were prepared according to an established protocol [13]. PEGDM, phosphate buffered saline (PBS, pH 7.4, Gibco), NFC and 0.1 g ml −1 % of Irgacure 2959 (BASF), were mixed as photoinitiator using ultra-turrax (IKA T25 digital, SN 25 10G).…”
Section: Hydrogels Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogel precursors were prepared according to an established protocol [13]. PEGDM, phosphate buffered saline (PBS, pH 7.4, Gibco), NFC and 0.1 g ml −1 % of Irgacure 2959 (BASF), were mixed as photoinitiator using ultra-turrax (IKA T25 digital, SN 25 10G).…”
Section: Hydrogels Synthesismentioning
confidence: 99%
“…The rheology results on PEGDM-NFC composite hydrogel precursor [13] showed that composite hydrogel is composed of two networks; a covalently bonded PEGDM network as well as the network of NFC fibers formed through physical entanglements and hydrogen bonds (see Fig. 5).…”
Section: Swelling Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversions of 30% or 50% might already be sufficient to achieve a sufficiently cured material. 28 As poly(ethylene glycol) (PEG)-base gels usually swell when immersed into water of PBS, 29 the increase in volume could also be attributed to swelling and not photopolymerization. Yet, the impact of dissolved PEG molecules on the ionic strength of the solvent is much higher than the impact of dissolved ions in the PBS (Na þ , Cl − , K þ , PO 3− 4 , etc.).…”
Section: In Situ Photopolymerization Monitoring Resultsmentioning
confidence: 99%
“…The polymerization was considered complete when G reached a plateau level. The time required to reach 95% of the plateau level of G was defined as polymerization time, noted t 95 , as previously reported (Khoushabi et al, 2015).…”
Section: Photopolymerizationmentioning
confidence: 99%